20E and MAPK signal pathway involved in the effect of reproduction caused by cyantraniliprole in Bactrocera dorsalis Hendel (Diptera: Tephritidae). Issue 1 (30th August 2021) - Li, Jianying; Liu, Jin; Chi, Baojie; Chen, Peng; Liu, Yongjie
Abstract: BACKGROUND: It is a common phenomenon that insecticides affect insect reproduction and insect hormones. After cyantraniliprole treatment, the egg production and remating behavior of female Bactrocera dorsalis were affected, a phenomenon of 'hormesis' appeared, but the change at the molecular level was unknown. Therefore, we investigated the fertility, insect hormone titers and transcription levels and used RNAi to prove the function of genes, to explore the molecular mechanism of cyantraniliprole causing reproductive changes in female B. dorsalis . RESULTS: LC20 treatment promoted egg production, while LC50 treatment inhibited it. Both high and low concentrations inhibited female ovaries' development and reduced the length of the ovarian tubes. Among insect hormones, only the titer of 20‐hydroxyecdysone (20E) changed significantly. According to the KEGG pathway enrichment analysis of RNA‐seq, there are significant differences in insect hormone synthesis and MAPK signal pathways between treatments. Furthermore, 20E biosynthetic genes, BdVgs and BdVgR were all down‐regulated, and multiple MAPK signaling pathway genes were up‐regulated. Based on qRT‐PCR, the expression of BdCyp307A1, BdCyp302A1, BdMEKK4 and BdMAP2K6 within 1–11 days after treatment were consistent with the change of 20E titer. The BdVg1 and BdVg2 in LC50 were still suppressed, while the LC20 returned to normal in 9–11 days. RNAi indicated that BdMEKK4 and BdMAP2K6 participated in the transcriptional regulation of BdCyp307A1 and BdCyp302A1, then affected the levels of BdVgs . CONCLUSION: Cyantraniliprole affected 20E through MAPK signal pathway, causing many genes to be down‐regulated during the early period but up‐regulated during the late period, ultimately affecting the reproduction of B. dorsalis . © 2021 Society of Chemical Industry. Abstract : Cyantraniliprole affects the biosynthesis of 20E through MAPK signal pathway and affects the oviposition and ovarian development of Bactrocera dorsalis .